The Bare Trust Syndrome In The Peninsular Malaysian Torrens System: A Harbinger Of Total Commitment To Equity? Or The Means Of A Return To Torrens Concepts? - Sihombing, Judith (Journal of Malaysian and Comparative Law, 2018)
A owns Torrens land and contracts to sell it to B. B pays the purchase price in full and receives a transfer in registrable form, the issue document of title and possession of the land. Prior to registration, what interest does B have?